A comparative analysis of global and Chinese trends in the burden of kidney cancer from 1990 to 2021 - Zhongli Qiao; Jun Xiong; Shenyu Zhang; Lin Chen; Jialin Wang; Runze Chen (Scientific Reports)
Abstract Kidney cancer, a prevalent malignant tumor in the urinary system, poses a significant disease burden and remains a crucial public health concern. Utilizing GBD(Global Burden of Disease)2021 data, our study examined the standardized incidence, mortality, prevalence, and DALYs(Disability Adjusted Life Years) rate of renal cancer. We calculated the [1-MIR(Mortality to Incidence Ratio)] value to assess treatment outcomes and survival rates, employed a joinpoint regression model to determine the AAPC(Average Annual Percentage Change), and conducted comparative and longitudinal analyses between China and global trends. The SII(Slope Index of Inequality) and the CI(Concentration Index) were used to assess the DALYs inequality caused by kidney cancer, and the SDI(Socio-demographic Index) was used as the basis for the ranking. Through the joinpoint regression model, we calculated the AAPC and conducted a comprehensive analysis of the disease burden of kidney cancer, evaluating its current status and changing trends. From 1990 to 2021, the age-standardized incidence rate, age-standardized mortality rate, age-standardized prevalence rate, and age-standardized DALYs rate of kidney cancer in China were lower than those the global average. However, the growth rate in China was significantly faster than the global average. The age-standardized incidence rate and prevalence rate of kidney cancer in males showed a greater increase compared to females, both in China and globally. Additionally, the age-standardized rate of kidney cancer in males was notably higher than in females, particularly among middle-aged males. The (1-MIR) of renal cancer increased from 0.36 to 0.62 in China and from 0.49 to 0.58 globally. Overall, the treatment effect of renal cancer has shown some successful outcomes. The SII decreased from 53.47 to 50.19, and the CI decreased from 0.342 to 0.289. The health inequality level of kidney cancer was significant but alleviated. From 1990 to 2021, there was a noticeable increase in the global incidence of kidney cancer. Specifically, the standardized incidence and prevalence of kidney cancer in the Chinese population saw a more rapid rise compared to the global average. Additionally, the disease burden of kidney cancer remained significantly higher in males than in females.